Technical Assistance Evaluation Program : Findings of Evaluations and Updated Program. (Policy Papers; Policy Paper ;, 2010)
The Kyrgyz Republic -- Joint Economic Assessment: Reconciliation, Recovery and Reconstruction; Prepared by the Asian Development Bank, International Monetary Fund, and The World Bank; With the participation of Eurasian Development Bank, European Bank for Reconstruction and Development, European Commission, International Finance Corporation, and The United Nations.